2003
DOI: 10.1080/10915810305081
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Approach for Iris Color Determination

Abstract: Latanoprost, the phenyl-substituted prostaglandin F2alpha, has been found to be an effective agent for glaucoma therapy. This prostaglandin derivative exerts ocular hypotensive activity but is also associated with an untoward side effect, namely iris color changes. Latanoprost provoked iris color changes in cynomolgus monkeys and in multicenter clinical trials. Until now photographs were taken and compared with color plates to document these changes. The disadvantage of this method is obvious, i.e., the color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Categorization of iris colour for genetic and epidemiology studies has been performed using a variety of descriptive terms either by self‐assessment with written criteria, the use of a trained observer for scoring, or grading by using defined photographic standards (Franssen et al., 2008; Seddon et al., 1990). Being somewhat subjective none of these methods are necessarily entirely reliable and as such automated photographic methods have been attempted to improve grading accuracy (Niggemann et al., 2003; Takamoto et al., 2001). One method using a digital camera and computer software to analyse light reflected from the iris has been described in detail, with the sum of a colour scale and a luminosity value used to derive a term called the Iris Melanin Index (IMI) suitable for ranking in population surveys but possibly concealing the details of iris patterns (Frudakis, 2008).…”
Section: Measures Of Iris Colour and Patternsmentioning
confidence: 99%
“…Categorization of iris colour for genetic and epidemiology studies has been performed using a variety of descriptive terms either by self‐assessment with written criteria, the use of a trained observer for scoring, or grading by using defined photographic standards (Franssen et al., 2008; Seddon et al., 1990). Being somewhat subjective none of these methods are necessarily entirely reliable and as such automated photographic methods have been attempted to improve grading accuracy (Niggemann et al., 2003; Takamoto et al., 2001). One method using a digital camera and computer software to analyse light reflected from the iris has been described in detail, with the sum of a colour scale and a luminosity value used to derive a term called the Iris Melanin Index (IMI) suitable for ranking in population surveys but possibly concealing the details of iris patterns (Frudakis, 2008).…”
Section: Measures Of Iris Colour and Patternsmentioning
confidence: 99%
“…Recently, there have been attempts to develop quantitative methods to estimate iris color based on photographs taken under standar-dized conditions. German et al (1998) andNiggemann et al (2003) reported iris pigmentation in the Red-Green-Blue (RGB) color space, and Melgosa et al (2000) quantified iris color using the CIELab color system. More recently, Fan et al (2003) have developed a method that automatically extracts the iris region from photographs, computes the iris color, and corrects the color based on a standard calibration target.…”
Section: Biochemical Measurements Of Melanin Contentmentioning
confidence: 99%
“…Commonly used technologies include tristimulus colorimetry, specialized narrow-band reflectometry, diffuse reflectance spectroscopy, digital photographs, and highperformance liquid chromatography (for a more systematic review on reflectometry and chromatography see [20]). Quantifying pigmentation phenotypes from digital photographs was proposed recently [21], and so far has been successfully applied to genetic studies of eye [18] and skin colors [19]. This method has obvious advantages in terms of cost, time efficiency, and portability, but -if not considered adequately in the design of the image collection -can also have disadvantages regarding noise variance being introduced by various source of environmental lights [22].…”
Section: Pigmentation Phenotypes: Quantification and Normalization Mamentioning
confidence: 99%